Enriched environment remodels the central immune environment and improves the prognosis of acute ischemic stroke in elderly mice with chronic ischemia - Zhang, Shehong; Zhang, Yonggang; Liu, He; Wu, Fengfeng; Wang, Zhihong; Li, Liqin; Huang, Huilian; Qiu, Sheng; Li, Yuntao (Frontiers in Immunology, 2023)
With the aging of the population, cognitive and motor dysfunction caused by ischemic stroke (IS) secondary to long-term chronic cerebral ischemia presents a global problem. Enriched environment (EE), a classic paradigm of response environment and genetic interaction, has shown tremendous influence on the brain. This research aimed to investigate the potential effect of EE on cognitive and motor function in mice with chronic cerebral ischemia and secondary IS. In the chronic cerebral hypoperfusion (CCH) phase, EE treatment improved the behavior performance by alleviating neuronal loss and white matter myelin damage, promoting the expression of brain-derived neurotrophic factor (BDNF) and phosphor-cAMP response element binding protein (p-CREB). Furthermore, infiltration of microglia/macrophages and astrocytes was inhibited, and the levels of IL-1β and TNFα were decreased. In the IS phase, EE altered the neuronal outcome on day 21 but not on day 1 after IS. In addition, EE inhibited IS-induced infiltration of microglia/macrophages and astrocytes, mediated the polarization of microglia/macrophages, and reduced pro-inflammatory factors. Importantly, EE improved IS-induced cognitive and motor deficits on day 21. Collectively, our work demonstrates that EE protects mice from cognitive and motor dysfunction and inhibits neuroinflammation caused by CCH and IS.